DAMPAK GREEN BANKING TERHADAP REPUTASI BANK DAN KEPERCAYAAN NASABAH - Pretty Naomi Sitompul; Fransiska Sirait (JURNAL LENTERA BISNIS, 2025)
In recent years, sustainability and environmental preservation have become primary concerns across various sectors, including banking. Green Banking is a banking strategy that incorporates environmentally friendly principles into its operations and policies, such as transaction digitalization, energy efficiency, and financing of sustainable projects. This study aims to analyze the influence of Green Banking on bank reputation and its impact on customer trust. The research applies a quantitative method with a survey approach involving 100 banking customers in Medan City. Data were analyzed using multiple linear regression and Sobel Test for mediation analysis. The findings indicate that Green Banking has a positive and significant effect on both bank reputation and customer trust—directly and indirectly through reputation. Bank reputation significantly mediates the influence of Green Banking on customer trust. These findings emphasize that sustainable banking practices not only enhance institutional image but also strengthen public trust in the banking sector